Antioxidative activities and isolation of phenolic compounds from the root, fruit and leaf of mengkudu (Morinda citrifolia L.) - Zamzahaila Mohd Zin (Universiti Putra Malaysia, 2011)
This study was conducted with the objective of evaluating the antioxidative activities of extracts from different parts of Mengkudu (Morinda citrifolia L.) including leaf, fruit and root. Methanol, petroleum ether, water and ethyl acetate were used as extraction solvent. The antioxidative activities assays were done using ferric thiocyanate method (FTC) and thiobarbituric acid test (TBA). Furthermore, the activities of these extracts were then compared to that of a-tocopherol and butylated hydroxy! tolune (BHT). Effect of solvent types and concentration of extract used on antioxidative activities of M. citrifolia were also carried out.